Peningkatan Kapasitas Pelatih dan Pembentukan Karakter Calon Pendekar di Organisasi Pencak Silat “Setia Hati Terate” Ranting Saradan, Daerah Khusus Pusat Madiun - Lailin, M.I.A.H; ZD, Ratnaningrum (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pencak silat is a local wisdom that is ingrained in line with the times. Pencak silat is an element of the personality of the Indonesian nation which is owned from the results of hereditary cultivation. Pencak Silat as spiritual/mysticism teaching is given to students who have advanced in studying their Pencak Silat knowledge. The goal is to improve the character or nobility of the students' mind. Pencak Silat has the goal of realizing harmony/balance/harmony/the surrounding environment to increase faith and piety to God Almighty, in order to fill Indonesia's national development in realizing a Pancasilaist complete Indonesian human being. To form this character, it is necessary to form qualified warriors and prospective warriors, not only mastering the art of pencak silat, but must be able to become leaders who are able to communicate with various parties. So an effort was made to provide material about increasing capacity in communication and in leadership. So that warriors and prospective warriors understand the procedures for communicating, Leadership and CMI (Cara Memberi Instruksi) which are very much needed in everyday life. In the future they can become skilled warriors and fighters.